randRange(1, 10) randRange(1, 10) randRange(1, 10) randRange(1, 10) randRange(1, 10)

Doprowadź poniższe wyrażenie do najprostszej postaci.

A + (B \times C)

A+B*C

= A + (B*C)

= A + B*C

= A+B*C

A + B \times C

A+B*C

= A + B*C

= A+B*C

A \times (B + C)

A*(B+C)

= A \times B+C

= A*(B+C)

A + (\dfrac{B*C}{C})

A+B

= A + (B)

= A + B

= A+B

A + \dfrac{B*C}{C}

A+B

= A + B

= A+B

\dfrac{ (A*(B+C)) }{ B + C }

A

= \dfrac{ (A*(B+C)) }{ ((B+C)) }

= \dfrac{ (A*(B+C)) }{ B+C }

= A

\dfrac{ (A*(B-C)) }{ (B - C) }

A

= \dfrac{ (A*(B-C)) }{ ((B-C)) }

= \dfrac{ (A*(B-C)) }{ B-C }

= A

(A + (B - C \times D)) \times E

(A+(B-(C*D)))*E

= (A + (B - (C*D))) \times E

= (A + ((B-(C*D)))) \times E

= (A + (B-(C*D))) \times E

= ((A+(B-(C*D)))) \times E

= (A+(B-(C*D))) \times E

= (A+(B-(C*D)))*E

A + (B - C \times D) \times E

A+((B-(C*D))*E)

= A + (B - (C*D)) \times E

= A + ((B-(C*D))) \times E

= A + ((B-(C*D))*E)

= A+((B-(C*D))*E)

A - B \times C + \dfrac{ (D*E) }{ E }

A-B*C+D

= A - B \times C + D

= A - (B*C) + D

= (A-B*C) + D

= A-B*C+D

A \times B + C \times \dfrac{ (D*E) }{ E }

(A*B)+(C*D)

= A \times B + C \times D

= (A*B) + C \times D

= (A*B) + (C*D)

= (A*B)+(C*D)

(A + B \times C) - D \times E

(A+B*C)-(D*E)

= (A + (B*C)) - D \times E

= (A+(B*C)) - D \times E

= (A+(B*C)) - (D*E)

= (A+B*C)-(D*E)